Comportamiento agronómico de la papa (Solanum Tuberosum L.) variedad superchola con la aplicación de tres tipos de abonos orgánicosen el cantón Latacunga. Quevedo - Cevallos Arcos, Milton Rodrigo (2013)
The present investigation is carried out in the search of an alternative to increase the production and productivity in the cultivation of potatoes, was carried out in the Tanicuchí parish, Latacunga canton, of Cotopaxi county whose geographical location is of 00°93´00´´ of south latitude and 78°61´00´´ of longitude west, with an altitude of 2955 msnm. The experimental work had duration of six months. The treatments were three payments organic gallinaza 5.265,00 Kg/ha-1, guano 5.265,00 Kg/ha-1 and bioabor 5.265,00 Kg/ha-1 like witness was used the chemical fertilizer 8-20-20 in dose of 800kg/ha-1, with four repetitions that you/they prepared at random in a Design of Complete Blocks (DBCA). To determine differences among the averages of the treatments, the test of multiple ranges was used from Tukey to 0.05% of probability. Of the results obtained in this investigation, he/she settles down that inside the agronomic behavior of potato's superchola cultivation, TO the 45 days after the one covers of the tubers, the treatment T2 has 100% of brotación of potato's tubers. The biggest plant height one has with the treatment T3 (Bioabor) 111.00 cm; The biggest quantity in tubers for plant 140.5 tubers; the biggest yield of potatoes 19.21 tm/ha-1; the smallest production cost and the biggest relationship benefit/coast 1.69 one has with the treatment T4 in which chemical fertilizer was used in dose of 800 kilos by hectare; and, within organic fertilizers the most benefit/coast shall T1 treatment corresponding to the application of 5625 kilos of gallinaza.